2018
DOI: 10.1088/1748-0221/13/11/p11015
|View full text |Cite
|
Sign up to set email alerts
|

Energy response of FD-7 RPL glass dosimeter compared with LiF Mg, Ti and Al2003:C dosimeters

Abstract: The aim of this study was to compare the energy dependence of Radio-Photoluminescent Glass Dosimeter (RPLGD) with thermoluminescent LiF:Mg,Ti (TLD-100) and Optically stimulated luminescent (Al2O3:C) dosimeters. In this work, a Monte Carlo simulation with MCNP5 was carried out to estimate the energy responses of these dosimeters. The following common clinical radiation qualities were applied: 50-300 kVp X-rays, 4-20 MeV electron beam and 60 Co γ rays as the reference. The current study is compared to previous m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 30 publications
1
5
1
Order By: Relevance
“…MC calculations has shown that globally the energy response decreases with the increase of the diameter for all three dosimeters: changing from a diameter of 1 mm to 13 mm decreases the energy response factor from 4.66 to 4.36 (6.4%), from 1.35 to 1.33 (1.5%) and from 3.61 to 3.31 (8.3%) for the RPLGD, TLD and OSLD, respectively. By comparing the results in this study with our previous work [3], we found a difference of 0.84%, 5% and 2.36% for RPLGD, TLD and OSLD, respectively. Also, MC calculations of the energy response for TLD, were carried out by Waldeland and Malinen [13].…”
Section: X-ray Beam Of 70 Kvsupporting
confidence: 66%
See 3 more Smart Citations
“…MC calculations has shown that globally the energy response decreases with the increase of the diameter for all three dosimeters: changing from a diameter of 1 mm to 13 mm decreases the energy response factor from 4.66 to 4.36 (6.4%), from 1.35 to 1.33 (1.5%) and from 3.61 to 3.31 (8.3%) for the RPLGD, TLD and OSLD, respectively. By comparing the results in this study with our previous work [3], we found a difference of 0.84%, 5% and 2.36% for RPLGD, TLD and OSLD, respectively. Also, MC calculations of the energy response for TLD, were carried out by Waldeland and Malinen [13].…”
Section: X-ray Beam Of 70 Kvsupporting
confidence: 66%
“…When the diameter changes from 1 mm to 13 mm, the energy response varies from 0.94 to 0.99, from 0.95 to 0.99 and from 0.91 to 1.00 for the RPLGD, TLD and OSLD, respectively. The comparison of the current MC values, for a diameter of 3 to 13 mmwith our previous work [3], shows a smaller difference of 2.48%, 0.51% and 4.01% for the three dosimetrs.…”
Section: Clinical Electron Beam Of 9 Mevcontrasting
confidence: 42%
See 2 more Smart Citations
“…Compared with TLDs, the first advantage of RPLGDs is their good reproducibility: luminescent centres are not eliminated by the reading process (i.e. the reading process is non-destructive) [1][2][3][4]. OSLDs have other advantages such as small size availability suitable for spot measurements, a wide range of linearity and high sensitivity, rapid reading resulting in high productivity and the use of relatively simple automated and semi-automated readers [5].…”
Section: Introductionmentioning
confidence: 99%